Politics, Networks and Community: Recruitment for the International Brigades Reassessed. (October 2020) - Raeburn, Fraser
Despite decades of scholarship, historians have struggled to explain the decision made by the tens of thousands of volunteers who joined the International Brigades during the Spanish Civil War (1936–9). Recent methodological innovations, particularly the embrace of transnational perspectives, have led to richer appreciations of complex individual motives and circumstances, but have done less to advance general explanations of the phenomenon. Drawing on a Scottish case study, this account argues that while motives may indeed have been highly individual, the context for the decision to enlist was not, with most volunteers coming from within well-defined social and political spheres. The density of recruitment among particular Communist Party networks suggests that far from being an internalised choice, the decision was made alongside and influenced by friends, family and colleagues. The communal nature of this process offers a useful explanation of the scale of recruitment for Spain across contexts, and suggests several specific factors that enabled the international communist movement to mobilise itself on such a large scale compared to other historical contingents of foreign fighters.